2014
DOI: 10.1097/yco.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

Review of the energy drink literature from 2013

Abstract: This review of recent literature focused on prevalence, motivation, and consequences of energy drink use. Clear findings emerged only on the dangers of mixing alcohol and energy drinks. The lack of a standardized measure made the comparison across studies difficult. Future research should extend and clarify these findings using standardized measures of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Alcohol mixed with energy drinks (AmED) is more hazardous compared to using either alcohol or energy drinks alone [ 23 ]. The previous literature reports that AmED relates to the use of tobacco, marijuana, and other stimulants [ 24 ] and leads to other undesirable consequences, such as increased alcohol consumption, risky sexual activities, and illegal driving [ 7 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol mixed with energy drinks (AmED) is more hazardous compared to using either alcohol or energy drinks alone [ 23 ]. The previous literature reports that AmED relates to the use of tobacco, marijuana, and other stimulants [ 24 ] and leads to other undesirable consequences, such as increased alcohol consumption, risky sexual activities, and illegal driving [ 7 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…240 mL) can [19], although it can be as high as 50–60 g [5], which can contribute to obesity and dental caries [19]. Mixing EDs with alcohol consumption (AmEDs) may result in health disorders (mostly from the cardiovascular system) and risk behaviour, such as drinking and driving, sexual abuse [20,21], excessive alcohol consumption, smoking, drug abuse and violence [22,23,24,25,26]. Many young EDs consumers do not know the composition of EDs and do not distinguish them from other sugar-rich soft drinks or beverages addressed to sports people [27].…”
Section: Introductionmentioning
confidence: 99%
“…Even though in our study a higher proportion of alcohol drinkers was detected among ED users, these habits were not found to be significantly associated in the regression analysis. However, previous studies have indicated that consuming EDs is connected to an excessive consumption of alcohol, even in other population groups [31,[36][37][38]. Thus, EDs users could be considered a risk group for alcohol abuse and its consequences such as palpitations and other cardiological issues [39].…”
Section: Discussionmentioning
confidence: 99%